2020
DOI: 10.1016/j.eplepsyres.2020.106414
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of ICD-10-CM claims-based definitions for epilepsy and seizure type

Abstract: Objective: To evaluate the accuracy of ICD-10-CM claims-based definitions for epilepsy and classifying seizure types in the outpatient setting. Methods:We reviewed electronic health records (EHR) for a cohort of adults aged 18+ years seen by six neurologists who had an outpatient visit at a level 4 epilepsy center between 01/2019-09/2019. The neurologists used a standardized documentation template to capture the diagnosis of epilepsy (yes/no/unsure), seizure type (focal/generalized/unknown), and seizure freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…We did not perform sensitivity analyses using alternative codes, which is a limitation. However, the ICD‐10 codes used in this study have been shown to have high rates of agreement with clinical records, at least for the comorbidities for which we found significant differences in risk [69–73]. We did not assess and control for the number or frequency of visits with the PCP, which might be a source of ascertainment bias, and could explain in part the increased frequency of comorbidities in younger MS patients.…”
Section: Discussionmentioning
confidence: 94%
“…We did not perform sensitivity analyses using alternative codes, which is a limitation. However, the ICD‐10 codes used in this study have been shown to have high rates of agreement with clinical records, at least for the comorbidities for which we found significant differences in risk [69–73]. We did not assess and control for the number or frequency of visits with the PCP, which might be a source of ascertainment bias, and could explain in part the increased frequency of comorbidities in younger MS patients.…”
Section: Discussionmentioning
confidence: 94%
“…Similar to prior work, [ 28 , 29 ] to identify prevalent treated epilepsy, we required at least one International Classification of Disease, Clinical Modification (ICD-CM) epilepsy/convulsion code (ICD-9 before October 1, 2015: 345.xx/780.3x; ICD-10 after October 1, 2015: G40/R56) plus at least one ASM fill in every year 2014–2016 (hence, appearance of at least three ICD codes, and sustained ASM treatment, over time; ASMs listed in Supplemental Table 1 ). Combining codes plus ASM fills in Medicare identified patients with epilepsy with an area under the curve 0.93, sensitivity 88%, and specificity 98% compared with reference gold standards of electronic medical records-based diagnosis by a blinded experienced neurologist using current International League Against Epilepsy guidelines [ 30 ].…”
Section: Methodsmentioning
confidence: 80%
“…We captured predictors such as those above, based on literature review and study team expert consensus possibly related to nonadherence [ 28 ] and discontinuation [ 40 ]. These included demographics (age, sex, race, Medicaid dual eligibility due to low income, rural ZIP code, [ 47 ] geographic region, reason for Medicare entitlement), clinical characteristics (dementia, depression, [ 48 ] Charlson comorbidity index, [ 49 , 50 ] number of ASMs, total number of medications, neurologist visit in 2015, yearly office visits for epilepsy), and epileptogenic neurological conditions in 2014–2015 (stroke, traumatic brain injury, intracranial hemorrhage, central nervous system tumor, meningoencephalitis, cardiac arrest; Supplemental Table 2 ), focal or generalized epilepsy, [ 29 ] and refractory epilepsy, [ 51 ] in 2014–2015.…”
Section: Methodsmentioning
confidence: 99%
“…The health care costs attributable to evaluation and management of epilepsy vary based on seizure types and levels of seizure control 39 . Future studies may use claims‐based approaches for defining seizure control and stratifying by epilepsy subgroups 40 . Our study could not differentiate patients with prevalent versus incident epilepsy, or well‐controlled epilepsy versus refractory epilepsy.…”
Section: Discussionmentioning
confidence: 97%